2017
DOI: 10.1016/j.physbeh.2017.01.039
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at the subordinate population within the visible burrow system

Abstract: The visible burrow system (VBS) utilizes the natural social behavior of rodents to model chronic social stress. Classically, when male and female rats are housed together in the VBS a dominance hierarchy rapidly forms with one dominant (DOM) and three subordinate (SUB) males. SUB animals show signs of chronic social stress, including loss of body weight and elevated basal corticosterone. This study furthered examined differences among the SUB population. Quantitative observations across numerous VBS colonies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…However, these effects may depend on the type of stressor one is exposed to. Recently, Melhorn et al (2017) demonstrated that OMEGA males, SUBs that experienced the most wounding and most severe body weight loss had significantly higher elevations of NPY mRNA within the amygdala that traditional SUBs. Whether this reflects a beneficial, but insufficient compensatory mechanism or a maladaptive one is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these effects may depend on the type of stressor one is exposed to. Recently, Melhorn et al (2017) demonstrated that OMEGA males, SUBs that experienced the most wounding and most severe body weight loss had significantly higher elevations of NPY mRNA within the amygdala that traditional SUBs. Whether this reflects a beneficial, but insufficient compensatory mechanism or a maladaptive one is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous VBS studies have demonstrated that SUB males have enhanced HPA axis activity and that this corresponds with elevated CRH mRNA expression within the paraventricular nucleus of the hypothalamus (PVN) and the central nucleus of the amygdala (CeA). Occasionally, one subordinate male will be the main recipient of attacks in the burrow, and is referred to as the OMEGA; OMEGA males incur more wounds, more severe weight loss and exhibit depressive-like behaviours at the end of the 2 wk VBS housing period (Melhorn et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Recent work from Melhorn (this issue) has further clarified the issue of heterogenity within subordinate subpopulations [16]. On the basis of wound burden and location, her study identifies a more severe subordinate stress group (referred to as Omegas) that have markedly potentiated weight loss relative to DOM and other subordinates (SRS), including rather marked loss of lean body mass.…”
Section: The Vbs Stress ‘Phenotype’mentioning
confidence: 99%
“…Importantly, identified Omegass are also stress hyporesponsive, having a negligible corticosterone response to restraint challenge. These data suggest the hierarchical structure extends beyond a single dominant and submissive phenotype, and that the Omega individuals may be the most severely affected of all groups [16]. …”
Section: The Vbs Stress ‘Phenotype’mentioning
confidence: 99%
See 1 more Smart Citation